Combined influence of carrier mobility and dielectric constant on the performance of organic bulk heterojunction solar cells - Inche Ibrahim, Mohd Lukman; Ahmad, Zubair; Sulaiman, Khaulah; Muniandy, S. V. (AIP Publishing, 2014)
It has been shown that there is an optimum charge carrier mobility that leads to a peak in the efficiency for organic bulk heterojunction solar cells with mobility-dependent recombination rate. Hence, improving the mobility is considered as one of the ways to increase the efficiency. In this study, we investigate the combined influence of charge carrier mobility and dielectric constant on the performance of organic bulk heterojunction solar cells by performing drift-diffusion calculations. We find that a higher dielectric constant leads to a higher peak efficiency together with a lower optimum mobility. We also find that if the dielectric constant of the active material can be increased significantly (to around 8 or higher), it is then possible that the mobility of the active material need not to be improved in order to achieve the maximum efficiency. This study demonstrates the importance of knowing the interplay between the mobility and the dielectric constant with regard to the efficiency. C 2014 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution 3.0 Unported License.